Evaluation of Error Production in Animal Fluency and Its Relationship to Frontal Tracts in Normal Aging and Mild Alzheimer’s Disease: A Combined LDA and Time-Course Analysis Investigation - Itaguchi, Yoshihiro; Castro-Chavira, Susana A.; Waterloo, Knut; Johnsen, Stein Harald; Rodríguez-Aranda, Claudia (Frontiers in Aging Neuroscience, 2022)
Semantic verbal fluency (VF) assessed by the animal category is a task widely used for the early detection of dementia. A feature not regularly assessed is the occurrence of errors including perseverations and intrusions. So far, no investigation has analyzed the how and when of errors’ occurrence during semantic VF in aging populations together with their possible neural correlates. The present study aims to address the issue by conducting a combined methodology based on the Latent Dirichlet Allocation (LDA) analysis for word classification together with a time-course analysis identifying exact time of errors’ occurrence. The LDA is a modelling technique that discloses hidden semantic structures based on a given corpus of documents. We evaluated a sample of 66 participants divided into: a young healthy group (n = 24), a healthy older adult group (n = 23) and a group of patients with mild Alzheimer’s disease (AD) (n = 19). We used DTI analyses to evaluate white matter integrity of three frontal tracts purportedly underlying error commission: anterior thalamic radiation, frontal aslant tract and uncinate fasciculus. Contrasts of DTI metrics were performed on the older groups who were further classified into high-error rate and low-error rate subgroups. Results demonstrated a unique deployment of error commission in the patient group characterized by high incidence of intrusions in the first 15 seconds and a higher rate of perseverations towards the end of the trial. Healthy groups predominantly showed very low incidence of perseverations. The DTI analyses revealed that AD patients committing high-error rate presented significantly more degenerated frontal tracts on left hemisphere. Thus, our findings demonstrated that appearance of intrusions together with a left-hemisphere degeneration of frontal tracts is a pathognomic trait of mild AD. Further, our data suggest that error commission of AD patients arise from executive and working memory impairments related partly to deteriorated left-frontal tracts.